Legal Review of Land Disputes in Urban Areas - Firayani Firayani (PT. Anagata Sembagi Education, 2024)
Land disputes in urban areas are increasingly complex legal issues due to the high economic value of land, population growth, and weak land administration. This article aims to analyze the factors causing land disputes in urban areas and review the application of agrarian law in resolving them. Through a qualitative approach with literature studies and normative legal reviews, this article examines the legal aspects, the role of state institutions, and obstacles in resolving land disputes. The findings show that land conflicts in urban areas are generally triggered by overlapping ownership, document falsification, and physical control without rights. On the other hand, the implementation of the Basic Agrarian Law (UUPA) has not been fully effective, especially in administrative arrangements and law enforcement. Dispute resolution is often hampered by lengthy legal processes, lack of coordination between institutions, and minimal protection for low-income communities. Therefore, integrated and participatory law-based agrarian reform is needed to create agrarian justice in urban areas.